SLEEP IN THE ELDERLY: HEALTHY SLEEP FOR HEALTHY AGEING - Hrnčić, Dragan (Medicinski podmladak, 2024)
Sleep is a vital physiological process in which humans spend almost one third of their lives. Contemporary lifestyles, shift work, social jet lag and environmental blue light pollution significantly compromise sleep quality in all age groups, especially in working adults and the elderly. Poor sleep quality has been demonstrated to be a risk factor for a number of diseases, from cardiovascular to neurological including malignancies. Aging has been identified to be connected with poor sleep quality, making the elderly people more vulnerable for development of a number of somatic and mental disorders. Low sleep quality in the elderly accelerates aging and increases a risk of development of aging-related pathologies. There is increased societal attempts to sustain well-being and preserve health in aged population with the concept of healthy aging being widely promoted and accepted. Healthy sleep has been recognized as one of the pillows of healthy ageing, especially in all policies related to Decade of Healy Aging. One of the major sleep –related issues in the elderly is difficulty to distinguish physiological effects of aging on sleep pattern from those sleep disruptions caused by primary sleep disorders, other diseases or medications. Poor sleep quality and impaired sleep hygiene are associated with increased risk of various chronic cardiovascular diseases. Moreover, healthy sleep is essential for cognitive functions and prevention of cognitive decline and memory impairments in the elderly. Relationship between neurodegenerative disorders and poor sleep quality seems to be bidirectional, what is extensively studied in Parkinson’s disease.  Regular physical activity should be considered as a component of sleep quality management strategies in the elderly, but also as a preventive strategy to preserve healthy sleep for healthy aging.
Keywords: sleep; heathy ageing; elderly; sleep quality; cardiovascular diseases; neurodegenerative disorders; Alzheimer’s disease; Parkinson’s disease; longevity